Modeling the radiative, thermal and chemical microenvironment of 3D scanned corals - Murthy, Swathi; Picioreanu, Cristian; Kühl, Michael (Frontiers in Marine Science, 2023)
Reef building corals are efficient biological collectors of solar radiation and consist of a thin stratified tissue layer spread over a light scattering calcium carbonate skeleton surface that together construct complex three dimensional (3D) colony structures forming the foundation of coral reefs. They exhibit a vast diversity of structural forms to maximize photosynthesis of their dinoflagellate endosymbionts (Symbiodiniaceae), while simultaneously minimizing photodamage, offer resistance to hydrodynamic stress, reduce attack by predators and increase prey capture and heterotrophic feeding. The symbiosis takes place in the presence of dynamic gradients of light, temperature and chemical species that are affected by the interaction of incident irradiance and water flow with the coral colony. We developed a multiphysics modelling approach to simulate the microscale spatial distribution of light, temperature and O2 in a coral fragment with its morphology determined by 3D scanning techniques. Model results compared well with spatial measurements of light, O2 and temperature under similar flow and light conditions. The model enabled us to infer the effect of coral morphology and light scattering in tissue and skeleton on the internal light environment experienced by the endosymbionts, as well as the combined contribution of light, water flow and ciliary movement on O2 and temperature distributions in the coral.